Hubungan Perilaku Sosial dengan Kebiasaan Makan pada Anak Status Gizi Kurang - Ni Putu Rika Listia Wati; I Ketut Andika Priastana (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2020)
Social behavior is an activity in dealing with other people including friends, teachers, parents as well as other relations. Social behavior is an important aspect in forming eating habits. It is because the selection of children’s meals can be influenced by friends as well as parents. Meanwhile, eating habits is a consumption pattern obtained because it occurs repeatedly. This study aimed at investigating the correlation between social behaviors and eating habits of children with malnutrition status in working area of Negara II Public Health Centre in 2019. The research design used in this study was correlation analysis. The populations in this research were 56 children under age of 3-5 years old with malnutrition status in the working area of Negara II Public Health Centre, Jembrana Regency. From the total population, 52 children chosen by using probability sampling technique especially simple random sampling technique were used as the samples in this study. The statistic test used in this research was Spearman’s Rho. As the result of this study, it was found that most of the children’s social behaviors with good category were 27 (51%) and children eating habits with good category were 39 (75%). Based on the statistic test, it was found that p = 0.000 (p < 0.05), then Ho was rejected. It could be concluded that there was a correlation between social behaviors and eating habits of children with malnutrition status.